Organoids and Their Use in Modeling Gut Epithelial Cell Lineage Differentiation and Barrier Properties During Intestinal Diseases - Gómez, Dianne Pupo; Boudreau, Francois (Frontiers in Cell and Developmental Biology, 2021)
Maintenance of intestinal epithelium homeostasis is a complex process because of the multicellular and molecular composition of the gastrointestinal wall and the involvement of surrounding interactive signals. The complex nature of this intestinal barrier system poses challenges in the detailed mechanistic understanding of intestinal morphogenesis and the onset of several gut pathologies, including intestinal inflammatory disorders, food allergies, and cancer. For several years, the gut scientific community has explored different alternatives in research involving animals and in-vitro models consisting of cultured monolayers derived from the immortalized or cancerous origin cell lines. The recent ability to recapitulate intestinal epithelial dynamics from mini-gut cultures has proven to be a promising step in the field of scientific research and biomedicine. The organoids can be grown as two- or three-dimensional structures, and are derived from adult or pluripotent stem cells that ultimately establish an intestinal epithelium that is composed of all differentiated cell types present in the normal epithelium. In this review, we summarize the different origins and recent use of organoids in modeling intestinal epithelial differentiation and barrier properties.